Technical efficiency and port competition: Revisiting the Bohai Economic Rim, China - Grace W. Y. Wang; Chen Gao (Journal of Risk and Financial Management, 2012)
The Bohai Economic Rim plays an important role in supporting China's economic growth. For this research, we selected nine main ports in the region to study whether intra-port competition or corporatization would improve efficiency. Using a panel fixed effect model and stochastic frontier model, we found that the technical efficiency of selected ports is significantly influenced by the time of the initial public offering than by regional competition. The results are supportive and encouraging for policy makers to move toward the decentralized port governance in China.
Keywords: D22; D24; 330; Technical efficiency; Port performance; IPO; Profitability